2007
DOI: 10.1021/jp0757762
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of Chromium Core−Shell Nanostructures on H−Si(100):  Evolution of Spherical Nanoparticles to Uniform Thin Film without and with Atop Hexagonal Microrods

Abstract: Electrodeposition in Cr(VI) and Cr(III) aqueous electrolytes is found to produce, respectively, granular and spherical core−shell nanoparticles on H-terminated Si(100). For the granular nanoparticles obtained by electrodeposition in CrO3 and H2SO4 electrolyte solution, both the morphology and number density remain discernibly similar while the particle size increases with increasing charge transfer. In the CrCl3 electrolyte, evolution of the spherical nanoparticles to homogeneous Cr films without and with atop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Moreover, it was shown recently that electrodeposition might be used to prepare metallic particles of various shapes. For example, it was demonstrated that granular Cr nanoparticles or hexagonal microrods could be obtained depending on the deposition conditions,21 and the synthesis of tetrahexahedral Pd nanocrystals with high Miller Index facets was demonstrated using a pulse electrodeposition method 22. Likewise, it was shown recently that Pt nanowire with preferentially‐oriented {100} surfaces could be prepared through template‐assisted deposition, using an anodic aluminum oxide membrane 23…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown recently that electrodeposition might be used to prepare metallic particles of various shapes. For example, it was demonstrated that granular Cr nanoparticles or hexagonal microrods could be obtained depending on the deposition conditions,21 and the synthesis of tetrahexahedral Pd nanocrystals with high Miller Index facets was demonstrated using a pulse electrodeposition method 22. Likewise, it was shown recently that Pt nanowire with preferentially‐oriented {100} surfaces could be prepared through template‐assisted deposition, using an anodic aluminum oxide membrane 23…”
Section: Introductionmentioning
confidence: 99%
“…TEM analysis) must be carried out to further support this outcome. Notwithstanding, it is worthy of mentioning that Zaho et al, 2 see Fig. 1 in this reference, reported the formation of quite similar Cr core-shell nanoparticles during the Cr electrodeposition onto H-Si(100) substrate from Cr(III) in aqueous electrolytes (10 mM CrCl 3 and 0.1 M NaClO 4 (pH ) 5.4-3.1).…”
Section: Ethalinementioning
confidence: 82%
“…Cr 2 O 3 NPs have been used to fabricate antibacterial, antifungal, antioxidant, anticancer, antileishmanial, antiviral, antidiabetic, photocatalytic agents, as well as in the manufacture of microelectronic circuits, sensors, solar energy collectors, and fuel cells. 1 Although chromium electrodeposition has been based on Cr(VI) or Cr(III) aqueous electrolytes for many years, 2 recently investigations have sought out new alternatives to avoid the toxicity that this process causes through release of Cr (VI) into other media, thus affecting human health and the environment. 3 Additionally, the narrow potential windows, electrodeposit embrittlement, poor current efficiencies, etc., are other disadvantages that must be considered when aqueous solutions are used.…”
mentioning
confidence: 99%
“…The ECM gets byproducts [11][12][13][14][15], which are hydrogen and sludge/cakes (metallic hydroxides or hydrated oxides) at a rate of 100-150 cm 3 per cubic centimeter of material removed in NaCl electrolyte [16]. Theoretically, these metallic hydroxides/hydrated oxides would have atomic sizes that could be used to extract metallic nanopowders and may be an effective byproduct for additive manufacturing industries.…”
Section: Introductionmentioning
confidence: 99%